2021
DOI: 10.1029/2019jc015843
|View full text |Cite
|
Sign up to set email alerts
|

Variance of Bottom Water Temperature at the Continental Margin of the Northern South China Sea

Abstract: Turbulent mixing in the ocean has been recognized as one of the key factors that controls the meridional overturning circulation (e.g. see the review of Wunsch and Ferrari (2004) and references therein) and heat budget (Ganachaud & Wunsch, 2000; Simmons et al., 2004). Furthermore, it dominates the transport of nutrients, pollutants, and sediments in the local biology and geomorphology (e.g. Leichter et al., 2003; McPhee-Shaw, 2006). Both the intensity and distribution of turbulent mixing largely affect predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Recent works showed that the continental slope waters of the SCS are full of energetic internal tides and internal waves (Zhao, 2014;Alford et al, 2015), active mesoscale eddies (Wang et al, 2003;Chen et al, 2011), topographic trapped waves (Quan et al, 2021;Wang et al, 2021), and other ocean processes. As a result, diapycnal mixing is usually enhanced in this region (Tian et al, 2009;Yang et al, 2016;Shang et al, 2017;Lu et al, 2021), which causes the bottom waters to tend to uniform vertically and forms an unstable BML that identified by the temperature profiles (Huang et al, 2021). Based on 201 fulldepth profiles of temperature-salinity and velocity collected from 2005-2012, Li et al (2022) suggested that the Luzon Strait and Zhongsha Island Chain are the two hotspots of thick BML in the SCS, which are consistent with the two mixing 'hotspots' places as indicated by their previous work (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent works showed that the continental slope waters of the SCS are full of energetic internal tides and internal waves (Zhao, 2014;Alford et al, 2015), active mesoscale eddies (Wang et al, 2003;Chen et al, 2011), topographic trapped waves (Quan et al, 2021;Wang et al, 2021), and other ocean processes. As a result, diapycnal mixing is usually enhanced in this region (Tian et al, 2009;Yang et al, 2016;Shang et al, 2017;Lu et al, 2021), which causes the bottom waters to tend to uniform vertically and forms an unstable BML that identified by the temperature profiles (Huang et al, 2021). Based on 201 fulldepth profiles of temperature-salinity and velocity collected from 2005-2012, Li et al (2022) suggested that the Luzon Strait and Zhongsha Island Chain are the two hotspots of thick BML in the SCS, which are consistent with the two mixing 'hotspots' places as indicated by their previous work (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%